International finance : - Gibson, Heather D (Longman, 1996)
The book integrates international financial theory and institutional detail to provide a concise survey of the international financial system. An introduction sets international finance in its historical context, and presents more specific coverage of adjustment and liquidity through a series of historical examples including the gold standard; the interwar experiences; the Bretton Wood system; the Smithsonian agreement and managed float. Two case studies present the institutional structure of international finance: Monetary Integration in the European Union, shows the practical application of exchange-rate systems; and the International Debt Crisis highlights the characteristics, underlying causes and management of debt and its implications for the international financial system